Enhanced hydrogen release of metal borohydrides M(BH4)n (M = Li, Na, Mg, Ca) mixed with reduced graphene oxide. (13th July 2016) - Nale, Angeloclaudio; Pendolino, Flavio; Maddalena, Amedeo; Colombo, Paolo
Abstract: Mixtures of light metal borohydrides M(BH4 )n, M = Li, Na, Mg, Ca and reduced graphene oxide (rGO) or graphite with molar ratio 70:30 were prepared by high energy ball milling. Samples were investigated with thermal programmed desorption (TPD) volumetric analysis to test their gas release profiles. The presence of rGO led to a lower decomposition temperature for every mixture and to a different gas-release profile compared to pristine borohydrides and mixtures with graphite. The onset of decomposition temperature was reduced by 200 °C for LiBH4, 360 °C for NaBH4, 130 °C for Mg(BH4 )2 and 50 °C for Ca(BH4 )2 . The comparison of XRD profiles of decomposed samples showed a different pattern for each metal cation, confirming an interaction of the decomposition products with rGO sheets and suggesting a different pathway for the decomposition reaction. Reduced graphene oxide was prepared by clean thermal treatment in H2 atmosphere from graphene oxide obtained by modified wet chemical synthesis, and its presence significantly affected the gas release performance. Highlights: Light metal borohydrides are mixed with reduced graphene oxide. Gas release proles are compared for borohydrides/graphite and/rGO mixtures. Decomposition products are investigated.